Motivation and the Psycho-Emotional Reaction of Volunteers in War-Time - Hapon, Nadiya; Chudzicka-Czupała, Agata; Żywiołek-Szeja, Marta; Dubniak, Zlatyslav; Ho, Roger (Journal of Education Culture and Society, 2024)
Aim. The aim was to study motivation functions and the psycho-emotional reaction to participation in volunteering in Polish and Ukrainian volunteers who assisted Ukrainian refugees at the beginning of the war in Ukraine in 2022.Methods. For the empirical study of volunteers, the team of authors developed the questionnaire. The Volunteer Functions Inventory VFI and the Depression Anxiety Stress Scales DASS were used. The significance of the differences between the mean results of the measured variables in the Polish and Ukrainian samples was tested using the Student's t-test. Volunteers' expectations of volunteer leaders were tested by analysing responses to the open exploratory question.Results. The article reveals similarities and significant differences between Polish and Ukrainian volunteers in their motives and psycho-emotional reactions to volunteering. A common motive for both samples is that they are not helping for the sake of their professional careers. Ukrainian volunteers had higher rates of protective, religious, and social motivation functions of volunteering. Polish volunteers had higher rates of motivation based on understanding and empowerment opportunities. Ukrainian volunteers scored higher than Polish volunteers on the depression, anxiety, and stress scales. Volunteers' motivation expectations of leaders indicate the importance for volunteers of leaders' adherence to values, openness of intentions and actions, and attentiveness to volunteers' difficulties.Conclusion. The survey results can be used in psychological training for volunteers, in planning the activities of volunteer leaders, and in developing new methods for studying volunteer motivation.